Information Technology And Healthcare Security In Maxillofacial Surgery For Diabetic Patients: Enhancing Patient Safety Through Integrated Nursing, Pharmacy, Radiology, And Psychology Practices (The Review of Diabetic Studies, 2024)
Background: The integration of information technology (IT) and healthcare security systems has transformed clinical operations across medical disciplines, including Oral and Maxillofacial Surgery (OMFS). For patients with diabetes, however, the intersection of digital systems and surgical management introduces unique clinical and security challenges due to their increased vulnerability to infection, delayed healing, and systemic complications.Objective: This review aims to explore the impact of information technology and healthcare security on maxillofacial surgery in diabetic patients, with particular emphasis on patient safety, data protection, and the supportive roles of nursing, pharmacy, radiology, and psychology.Methods: A narrative review design was adopted. Studies published between 2010 and 2024 were retrieved from PubMed, Scopus, ScienceDirect, and Web of Science using terms related to “healthcare security,” “information technology,” “maxillofacial surgery,” and “diabetes.” Articles meeting inclusion criteria were thematically analyzed following Braun and Clarke’s (2006) framework.Results: Thirty-two studies were reviewed. Findings indicate that IT integration improves diagnostic accuracy, clinical coordination, and documentation efficiency. Nevertheless, unintended consequences such as workflow interruptions, data breaches, and alert fatigue remain prevalent. Cybersecurity gaps in OMFS settings pose risks to patient privacy and perioperative safety, particularly among diabetic patients requiring continuous multidisciplinary management.Conclusion: Information technology and healthcare security systems are critical in enhancing surgical safety and data reliability in diabetic maxillofacial patients. However, without robust cybersecurity frameworks and interdisciplinary digital standards, such systems may inadvertently compromise care. Future strategies should prioritize AI-based risk monitoring, cybersecurity training, and unified digital documentation across all clinical departments to support safe, efficient, and secure patient outcomes.